Synthesis and application of ZnO-MgO-NiO@Stearicamide mixed oxide for removal of ciprofloxacin and ampicillin from aqueous solution - Olamide A. Olalekan (Elsevier Results in Chemistry, 2022)
The presence of ciprofloxacin (CIP) and ampicillin (AMP) as emerging contaminant in water is a serious global challenge requiring affordable and sustainable solution. In response to this, this study prepared a mixed metal oxide, zinc oxide (ZnO)-magnesium oxide (MgO)-nickel oxide (NiO)@stearicamide for the removal of CIP and AMP from aqueous solution. The properties of ZnO-MgO-NiO@Stearicamide were confirmed with several analyses including Fourier transformed infrared spectroscopy (FTIR), Brunauer-Emmett-Teller (BET), transmission electron microscopy (TEM), X-ray diffraction (XRD) and energy-dispersive X-ray spectroscopy (EDX). ZnO-MgONiO@ Stearicamide has a BET surface area of 13.50 m2 g􀀀 1 and an average particle size of 12.50 nm. The sorption of CIP and AMP from solution by ZnO-MgO-NiO@Stearicamide showed a removal of 83.87 % and 81.10 %, respectively in a process that can be described by the Langmuir isotherm and electrostatic interaction. The sorption process has enthalpy (ΔH), entropy (ΔS) and free energy change (ΔG) which suggests the process to be spontaneous and exothermic. It is also found that synthesized metal mixed oxide could maintain a regeneration capacity that is > 80 % even after 11th regeneration cycle. The experimental findings indicate that the selfsynthesized ZnO-NiO-MgO@Stearicamide is a potential material to treat CIP- and AMP-contaminated water source.